2017
DOI: 10.1177/1077546316685680
|View full text |Cite
|
Sign up to set email alerts
|

A method for evaluating the comfort during blasting vibration based on energy absorbing principle

Abstract: Vibration from blasting operations exert negative effects on the comfort of nearby buildings (structures) resulting in the dissatisfaction of and even complaints from nearby residents. This problem impacts both blasting activities and social stability. Therefore, establishing a method for reasonably evaluating blasting vibration (BV) comfort and a standard can significantly reduce the complaints and civil disputes caused by construction activities involving blasting. This paper systematically reviewed the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…As seen in this figure, the DF of blasting waves is almost in the range of 11–60 Hz, especially between 15 and 30 Hz for surface blasting in these two rock formations. Obtained results comply well with the other similar research works in this field (Kahriman, 2002; Qiang et al, 2017; Tripathy et al, 2016). The important issue is that the DF range of blasting waves in these two rock types and some different rock formations investigated by other researchers is higher than 10 Hz, which is not within the natural frequency range of the typical residential structures.…”
Section: Coupled Effects Of Frequency Velocity and Displacementsupporting
confidence: 91%
“…As seen in this figure, the DF of blasting waves is almost in the range of 11–60 Hz, especially between 15 and 30 Hz for surface blasting in these two rock formations. Obtained results comply well with the other similar research works in this field (Kahriman, 2002; Qiang et al, 2017; Tripathy et al, 2016). The important issue is that the DF range of blasting waves in these two rock types and some different rock formations investigated by other researchers is higher than 10 Hz, which is not within the natural frequency range of the typical residential structures.…”
Section: Coupled Effects Of Frequency Velocity and Displacementsupporting
confidence: 91%
“…rough the above analysis, it can be found that those comparison factors like crack, flatness, and damage are all related to excavation quality, whose influences are limited to the vicinity of the explosive source. Nevertheless, in practice, residents in the neighborhood are more concerned about the adverse impacts of blast-induced vibrations because they can propagate over long distances [24][25][26][27]. Hence, it is vital to investigate the vibration characteristics induced by blasting operations with two control techniques.…”
Section: Introductionmentioning
confidence: 99%
“…When the blasting seismic waves are transmitted to the floor or seats that are in contact with the body, the vibration energy is transferred into the body, and the energy is transmitted along the body. Energy transfer and conversion concepts can be used to evaluate the vibration response of the human body, which is referred to as the "absorbed blasting vibration energy (ABVE)" [33]. The ABVE can be used as a parameter to characterize the interaction between humans and the vibration environment.…”
Section: Absorbed Blasting Vibration Energy (Abve)mentioning
confidence: 99%
“…Hence, the vibration signals with higher frequencies can cause a variety of bad human subjective experiences. In addition, for the vibration generated by the open-air blasting, the energy of ground motion is mainly concentrated in the high frequency band (i.e., 4∼80 Hz), which is the main component of the blasting vibration energy [33].…”
Section: Human Body Frequency-weighted Response Energymentioning
confidence: 99%